Contesting the Visualization of Gaza. (2nd January 2016) - Ramamurthy, Anandi
Abstract : During July‒August 2014 it is estimated that Israel dropped 18‒20, 000 tons of explosives on Gaza, which led to the deaths of over 2, 100 people, with homes, hospitals, schools and whole districts obliterated to rubble. Photographs played a crucial role in mediating this devastation within corporate media, social media as well as in street protests and pickets. Through an analysis of imagery used in BBC news reports for the first day of the bombing, this paper explores the dominant visual discourses in the mainstream media, which through both regulatory frameworks as well as political positioning supported Israeli PR agendas, to normalize Israeli perspectives and reinscribe Palestinians as both political and social "other". It then considers the success with which citizens both within Gaza and outside — as protestors and journalists — acted to challenge the corporate media's control over the visual mediation of the bombing. While recognizing that photographs of abject suffering can operate to simply consolidate an image of Palestinians as "other" and different from ourselves, the article argues that through employing Ariella Azoulay's notion of a "citizenry of photography" and reflecting on the wider communication ecologies in which photographs operated (on social media and in street protests), we can identify the ways in which images of suffering, placed in personal narratives and within a wider visual discursive field did play a role in influencing the public's understanding of the Palestinian plight, turning despair to indignation to demand action.